A NOVEL MODIFIED CASCADED MULTILEVEL INVERTER WITH OPTIMAL NUMBER OF CONSTANT ACTIVE SWITCHES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
As of late utilization of multilevel inverters (MLI) are expanded for high power mechanical applications. This paper introduces a changed cascaded MLI for 31-levels utilizing optimal number of constant active switches at any given purpose of time. The circuit comprises of arrangement associated sub cell which are utilized to deliver positive levels. H-extension is further associated with circuit to create alternative waveform. Power supply of this circuit is in binary arrangement. Voltage balancing issue is comprehended by utilizing this setup. Selective Harmonic Elimination is utilized to ascertain the switching pulses for MOSFETS. MATLAB/SIMULINK is utilized for logical investigation of the circuit.